Data from: Population genomic diversity and structure at the discontinuous southern range of the Great Gray Owl in North America - Mendelsohn, Beth; Ernest, Holly (Zenodo, 2020)
Species' distributions are often discontinuous near the edge of the range where the environment may be more variable than the core of the range. Range discontinuity can reduce or cut off gene flow to small peripheral populations and lead to genetic drift and subsequent loss of genetic diversity. The southern extent of the Great Gray Owl ( Strixnebulosa) range in North America is discontinuous, unlike their northern core range across the boreal forests. We sampled owls from five different locations on the periphery of the range across the western US (Wyoming, Idaho, California, northern Oregon, and southern Oregon) to investigate genetic population structure and genetic diversity. Using a reduced-representation genomic sequencing approach to genotype 123 individuals at 4,817 single nucleotide polymorphic loci, we identified four genetically differentiated populations: California, southern Oregon, northern Oregon, and Wyoming and Idaho grouped together as a single Rocky Mountain population. The four genetically differentiated populations of Great Gray Owls identified in this study display high differentiation and low genetic variation, which is suggestive of long-term isolation and lack of connectivity, potentially caused by range discontinuity. The populations that lack habitat connectivity to the rest of the breeding range (i.e. those in California and Oregon) had lower genetic diversity than the Rocky Mountain population that is connected to the core of the range. These factors and other risks (such as disease and human-caused mortality) heighten susceptibility of these range-edge populations to future habitat and climate changes, genetic diversity erosion, and potential extinction vortex. For these reasons, protecting and monitoring this species on the southern edge of their range is vital. File Descriptions: individual_IDs.xlsx: assigned ID codes for each individual and the state the sample was collected sample_information.xlsx: location data (approximate) where each sample was collected, date collected, ...